(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes the experience of implementing an effective model of state property privatization in Romania — the investment fund "Fondul Proprietatea." It examines approaches to enterprise transformation, opening them to international investors through the fund, and attracting capital via IPO and SPO mechanisms. Furthermore, a comparison is made with the activities of the "National Investment Fund" established in Uzbekistan, and scientific-practical recommendations are provided for deepening the privatization process.